The Role of Clinical Supervisors in Clinical Nursing Education: A Literature Review - Musharyanti, Lisa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
ABSTRACTThe success of clinical education is influenced by many factors, one of which is the clinical supervisor. Clinical supervisors have an important role during the student education process as teachers, facilitators, assessors, and as role models. All of these roles contribute to helping students achieve competence in both hard skills and soft skills to be ready to become professional nurses. This literature review aims to further examine the role of clinical supervisors in nursing education for nursing students. This literature review is a literature study by searching using keywords: (role AND clinical AND supervisor AND clinical AND education AND nurse) ALL (role AND clinical AND supervisor AND clinical AND education AND nurse) in the database: Pubmed (37), Science Direct (135), Scopus (252), and Google Scholar (2) articles. Then the articles were selected based on the inclusion and exclusion criteria and 7 articles were included in the PRISMA chart and Extraction Table. There were 7 articles that met the criteria and were extracted, some of the clinical supervisor roles found included teaching, utilizing literature from various sources, as a facilitator, encouraging critical thinking, confidence, developing skills in decision making, solving problems, providing support or motivation and appreciation, monitoring or assessing, therapeutic communication, building trusting relationships and being a role model.